Effectiveness Study of Blockchain Technology in Higher Education - Akhtary, Engila; Akhtari, Freshta (Technium Social Sciences Journal, 2022)
Abstract: A Blockchain is a chain of blocks that contains information. It was originally created for the purpose of scheduling digital documents so that it is no longer possible to change the date and access information. Store and share information such as knowledge, skills, credentials, etc. This was a safe way for no one else to access the information. Using Blockchain validate credentials reduces costs, eliminates fraud, and facilitates credit for higher education institutions, and learning this technology also leads to lifelong learning and skills development. The objective of this paper is an overview and it is effectiveness of Blockchain technology in higher education field. And in order to achieve our goal, we addressed the following questions: Does the use of Blockchain technology increase data security? Does the use of blockchain technology maintain the effectiveness and integrity of the data? Blockchain technology has attracted the attention of researchers and physicians, mainly due to its unique features such as decentralization, security, reliability and information integration. One of the most attractive applications fields for Biockchain is the Education, giving to us the possibility of many educational applications such as Certificate management, Identity verification, Protection of Intellectual property and record keeping. The Blockchain technology changed the security, increasing validity &efficiency of the education sector. the effectiveness of blockchain technology in higher education shows that the use of this technology increases the security of information in educational systems, as well as Using blockchain technology increases the credibility and efficiency of educational departments in higher educations.